An Overview Of Adolescents’ Levels Of Knowledge And Attitudes Toward Reproductive Health In The Children And Youth Fellowship (Par) Of Marthen Luther Church, Sentani - Adriano Manuel Kloatubun; Elepina Wisal; Tenna Wasini; Bawas Nabyal; Ironius Baransano; Meilinda Handayani Pasaribu (International Journal of Health Engineering and Technology, 2026)
Adolescence is a transitional period of physical and mental development that is vulnerable to risky sexual behavior due to a lack of understanding regarding reproductive health. Religious institutions, such as the Child and Youth Fellowship (PAR), have a strategic role as a health education medium based on moral values. This study aims to analyze the level of knowledge and attitudes of adolescents toward reproductive health at PAR Marthen Luther Church, Sentani. This research is a quantitative descriptive study with a cross-sectional approach. The study population consisted of all members of PAR Marthen Luther Church, Sentani, using a total sampling technique with 38 respondents. Data were collected using structured questionnaires. Knowledge assessment criteria were categorized into good (76-100%), moderate (60-75%), and poor (<60%), which were then analyzed univariately. The results showed that respondents' knowledge level was in the Good category in the aspects of understanding reproductive health (100%), reproductive organs (80%), fertile period and pregnancy (100%), maintenance of reproductive organs (80%), reproductive health problems (78%), sexual growth and development (75%), as well as menstruation and wet dreams (75%). However, the Moderate category was found in the aspects of adolescent nutrition (72%) and access to information (66.7%). Regarding attitudes, respondents showed positive results with an average achievement of 82%, where 97.4% of respondents supported the church as a place for reproductive health discussions. In general, respondents possess a good level of knowledge and attitudes, yet their understanding of how to access health information and nutrition still needs to be improved. This support indicates the importance of collaboration between health programs and the Child and Youth Fellowship to enhance the understanding of reproductive health.